Digital Religious Literacy and the Promotion of Religious Moderation through Islamic Education Learning among Senior High School Students - Anggi Wulandini; Mambaul Ngadimah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The development of digital media has transformed the way students acquire religious information. On the one hand, digital media expands access to religious knowledge; on the other hand, it has the potential to disseminate non-credible information and influence students’ religious attitudes. This study aims to analyze students’ digital religious literacy in Islamic Religious Education (IRE) learning and its implications for strengthening religious moderation. The study employed a qualitative approach using a case study method conducted at SMA Negeri 1 Babadan, Ponorogo. The participants consisted of one Islamic Religious Education teacher and five eleventh-grade students selected through purposive sampling. Data were collected through observation, interviews, and documentation and were analyzed using the interactive analysis model. The findings reveal four main themes. First, there has been a transformation in the sources and construction of students’ religious literacy, shifting from a teacher-centered model to the utilization of diverse digital sources. Second, critical digital literacy enhances students’ religious understanding through practices of information verification, source comparison, and confirmation of religious information. Third, Islamic Religious Education teachers serve as epistemic guides who assist students in identifying credible religious sources while integrating digital media into the learning process. Fourth, digital religious literacy contributes to strengthening students’ understanding of religious moderation by fostering tolerance, openness, and respect for diversity. The study concludes that digital religious literacy has the potential to reinforce religious moderation when supported by students’ critical thinking skills and adequate teacher guidance in navigating the digital environment.